Defense Information Systems Architecture for Cyber Threats: A Systematic Review of the Research Literature - Martanto Dwi Saksomo Hadi; Rudy Agus Gemilang Gultom; Ansori; Bambang Kustiawan (Postgraduate, University of Mataram, 2025)
Cyber ​​threats have become a serious challenge to national defense. Although Indonesia has a high cybersecurity index, a series of significant incidents against government institutions indicate urgent vulnerabilities that need to be addressed through a more resilient defense architecture. This study conducted a systematic literature review (SLR) to identify the results and practices of implementing the TOGAF, DoDAF, and COBIT (TDC) frameworks in the cyber defense domain. The results indicate that the literature is dominated by qualitative studies (53%) and COBIT framework implementations (73%), especially in government agencies (67%). The analysis yielded four main themes: improved governance and compliance, optimized risk management, strengthened security posture, and architectural and operational efficiency. The literature's focus on the first two themes signals a strategic shift from technical solutions to a governance- and risk-based approach. The study concludes that an effective approach to modern cyber defense is through integrating the specific strengths of each framework: COBIT for governance, DoDAF for operations, and TOGAF for architecture.